Sustentabilidade na Amazônia: abordagens acerca da produção de soja, carne bovina e castanha-do-Brasil - Schneider, Adriane Terezinha (2024)
Incorporating sustainability practices into food production in the Amazon becomes essential to guarantee food security and the preservation of natural resources. Considering the fact that food production is directly linked to the three pillars of sustainability (environmental, economic, and social), achieving an integral balance between them is crucial. In this sense, a careful analysis of these factors can elucidate key points throughout the production life cycle, allowing the identification of opportunities to promote sustainability further and minimize negative impacts. Given this, the work had the following objectives: (i) to evaluate the carbon footprint of these products obtained in the region, (ii) to analyze the economic aspect of food production in the biome, and (iii) to evaluate the potential social impacts related to these commodities in the northern region of Brazil. The results obtained demonstrate that the production of beef and soybeans presented greater environmental burdens in terms of carbon footprint when compared to the production of Brazil nuts with emissions in the order of 4.75 tCO2eq/ha, 1.0 tCO2eq/ha and 0.23 tCO2eq/ha, respectively. The economic aspect of the extractive production of Brazil nuts presented the highest net profit per hectare/year (USD 559.21), followed by soybeans (USD 533.94) and beef (USD 64). Regarding the social aspect of the production of commodities analyzed, in general, the negative impacts are linked to the production of beef cattle, in the subcategory of forced labor and gender equality, and the positive impacts are related to the production of soybeans, related to the subcategory of wages and benefits. Finally, the results of this work provide important information on the production of commodities in the Amazon biome, highlighting the contribution to the sustainability of the food production chain.